Efficacy and safety of aniseed powder for treating gastrointestinal symptoms of COVID-19: a randomized, placebo-controlled trial - Mosaffa-Jahromi, Maryam; Molavi Vardanjani, Hossein; Fuzimoto, Andrea; Hunter, Jennifer; Lankarani, Kamran Bagheri; Pasalar, Mehdi (Frontiers in Pharmacology, 2024)
Background: Gastrointestinal symptoms are prevalent amongst patients with a confirmed diagnosis of COVID-19 and may be associated with an increased risk of disease severity. This trial aimed to evaluate the efficacy and safety of aniseed (Pimpinella anisum L.) powder as an add-on therapy to standard care for treating gastrointestinal symptoms experienced by adults with an acute SARS-CoV-2 infection.The study was a randomized parallel-group double-blinded placebo-controlled add-on therapy trial. Adults with an acute SARS-CoV-2 infection who did not require hospitalization and reported at least one gastrointestinal symptom in the preceding 48 hours were assigned to either the aniseed or placebo group in a 1:4 ratio. All 225 participants (45 in the aniseed group and 180 in the placebo group) were instructed to use 25 grams of powdered aniseed or placebo twice daily for two weeks. The primary outcomes were the proportion of patients who experienced an improvement of at least one point in the symptom score after adjusting for age group, gender, and time. Backwards stepwise logistic regression was applied to calculate the risk ratios. The clinical symptoms and adverse events were assessed at the beginning, one week later, and at the end of the trial (week two).Results: Participants in the aniseed group were significantly more likely to report symptom improvement for abdominal pain (adjusted risk ratio (RR):0.55; 95% confidence interval (CI): 0.46 to 0.72), anorexia (RR:0.62; 95% CI: 0.47 to 0.82), and diarrhea (RR:0.19; 95% CI: 0.12 to 0.30), but not nausea/vomiting (RR:0.87; 95% CI: 0.71 to 1.08) or bloating (RR:0.87; 95% CI: 2 0.72 to 1.05). Two participants in the aniseed group and three participants in the placebo group reported mild to moderate adverse events.This study showed that two weeks of aniseed powder containing trans-anethole (87-94%) may help improve abdominal pain, anorexia, and diarrhea in COVID-19 patients. The findings align with the known biological, multitargeted activity of P. anisum and trans-anethole, which includes inhibiting SARS-CoV-2 along with other anti-infective, anti-inflammatory, antioxidant, hepatoprotective, and anti-dysbiosis properties. Multicenter trials with larger sample sizes and longer follow-up are warranted to confirm these findings.